Effects of Platelet-Rich Plasma in Tear Size Reduction in Partial-Thickness Tear of the Supraspinatus Tendon Compared to Corticosteroids Injection - Thanathep Tanpowpong; Marvin Thepsoparn; Numphung Numkarunarunrote; Thun Itthipanichpong; Danaithep Limskul; Phark Thanphraisan (SpringerOpen, 2023)
Abstract Objectives Corticosteroid (CS) injection is commonly used in partial-thickness rotator cuff tears to decrease pain. However, this could result in unwanted side effects, such as tendon rupture. Alternatively, platelet-rich plasma (PRP) injection is frequently used to treat tendinopathies because it enhances healing. This study aimed to compare the differences in tear size and functional scores between intralesional PRP and subacromial CS injections. Methods Patients with symptomatic partial-thickness tears of the supraspinatus tendon who underwent conservative treatment for ≥ 3 months were enrolled. All patients underwent magnetic resonance imaging (MRI) to confirm the diagnosis. Fourteen and 15 patients were randomized to receive intralesional PRP and subacromial CS injections, respectively. Tears were measured in the coronal and sagittal planes. The patients underwent another MRI 6 months after the injection. Tear size was compared between the two MRI results. The American Shoulder and Elbow Surgeons Shoulder score (ASES) and Constant-Murley score (CMS) were also obtained. Results The baseline data were similar between the groups. In the coronal plane, PRP and CS showed tear size reductions of 3.39 mm (P = 0.003) and 1.10 mm (P = 0.18), respectively. In the sagittal plane, PRP and CS showed tear size reductions of 2.97 mm (P = 0.001) and 0.76 mm (P = 0.29), respectively. Functional scores improved 6 months after injection in both groups, but PRP showed better functional scores than CS (P = 0.002 for ASES, P = 0.02 for CS). Conclusion Intralesional PRP injection can reduce the tear size in partial-thickness tears of the supraspinatus tendon. Subacromial steroid injection did not significantly affect the tear size. While CS improved functional scores compared with baseline, PRP resulted in better improvement 6 months post-injection. Trial registration Thai Clinical Trials Registry, TCTR20210428004. Registered 28 April 2021-retrospectively registered, TCTR20210428004 .